Translating Ukrainian War Poetry into English: Why It Is Relevant - Ivashkiv, Roman (East/West)

(untitled) (Canadian Institute of Ukrainian Studies University of Alberta, 2022)
This article explores the English translations of contemporary Ukrainian war poetry featured in the two anthologies Lysty z Ukrainy (Letters from Ukraine, 2016) and Words for War: New Poems from Ukraine (2017), through the prism of Jacques Derrida’s concept of “relevant.” It argues that although the economy of the original poems could not always be sustained, these translations nonetheless remain relevant primarily thanks to what they do rather than what they say. After contextualizing the recent (re)emergence of war poems as a genre of Ukrainian literature and providing an overview of the two translation anthologies, the article compares the Ukrainian originals with their English translations and discusses the various translation challenges. It then returns to Derrida’s own case study to extend the modifier “relevant” beyond its “economic” parameters to apply it more broadly to translation’s socio-political significance. It concludes with a discussion of how the two anthologies in question reflect the state of the reception of contemporary Ukrainian literature in the English-speaking world and how the translations they feature inform our understanding of the (un)translatability of poetry.